An innovative phase I study in healthy subjects to determine the mass balance, elimination, metabolism, and absolute bioavailability of mitapivat - Chandra Prakash; Heidi Mangus; Yan Yan; Hua Yang; Varsha Iyer (Wiley, 2023)
Abstract Mitapivat, a first‐in‐class, oral, small‐molecule, allosteric activator of the red blood cell‐specific form of pyruvate kinase (PKR), was approved for the treatment of hemolytic anemia in adults with pyruvate kinase (PK) deficiency. In this phase I mass balance study in healthy males, we administered a single ~120 mg oral dose of [14C]mitapivat and a concomitant intravenous ~0.1 mg microdose of [13C6]mitapivat. We determined (1) the routes of total radioactivity excretion, including the mass balance of total radioactivity in urine and feces; (2) the pharmacokinetics of mitapivat and [13C6]mitapivat in plasma and total radioactivity in whole blood and plasma; (3) the absolute oral bioavailability of mitapivat; and (4) the metabolite profiles in plasma and excreta. Mean recovery of the radioactive dose was 89.1% (49.6% in urine and 39.6% in feces). [14C]Mitapivat was rapidly absorbed and extensively metabolized as <4% of the total radioactive dose was excreted unaltered in urine and feces. Mean absolute oral bioavailability was 72.7%. A total of 17 metabolites were identified. Mitapivat accounted for 57% and 34% of plasma radioactivity in AUC0-24 and AUC0-72 pooled samples, respectively. The remaining radioactivity was attributable to several metabolites, each representing <10% of the total radioactivity in pooled samples; none were disproportionate metabolites as defined by the US Food and Drug Administration and International Conference on Harmonisation M3 guidelines. Metabolite structures suggest that the primary metabolic pathways for [14C]mitapivat in humans include N‐dealkylation of the cyclopropylmethyl moiety, oxygenation of the quinoline‐8‐sulfonamide, oxidation/unsaturation, scission of the piperazine moiety, and amide hydrolysis.